2019
DOI: 10.1111/psyg.12450
|View full text |Cite
|
Sign up to set email alerts
|

Association between longitudinal clinical outcomes in patients with hip fracture and their pre‐fracture place of residence

Abstract: Background: Clinical outcomes of patients with proximal femoral fracture within 1 year after hospitalization are presented. In particular, associations between the patients' clinical status and their pre-fracture residence were evaluated (community-dwelling vs nursing home). Methods: Patients aged ≥60 years with proximal femoral fractures were included in a prospective, single-centre observational study and followed for 12 months. Patients' clinical status at baseline was compared to their health status at fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…e need for these adjusted algorithms and appropriate tracker devices is in accordance with studies, showing distinctive validity for different wearables and intensities [32,33]. e clinical improvement observed between operation and discharge could be documented with a similar quality as the usually applied indices for quality of life (EQ5D) and functional independence (Barthel-20), which are regarded as the current gold standard [34]. However, only the measured activity parameters of the highest level out of 4 corresponding with actual walking or active or very active minutes were able to delineate this development.…”
Section: Discussionmentioning
confidence: 58%
“…e need for these adjusted algorithms and appropriate tracker devices is in accordance with studies, showing distinctive validity for different wearables and intensities [32,33]. e clinical improvement observed between operation and discharge could be documented with a similar quality as the usually applied indices for quality of life (EQ5D) and functional independence (Barthel-20), which are regarded as the current gold standard [34]. However, only the measured activity parameters of the highest level out of 4 corresponding with actual walking or active or very active minutes were able to delineate this development.…”
Section: Discussionmentioning
confidence: 58%
“…A proximal femoral fracture further diminishes HRQoL. Among nursing home residents who were surgically treated for their injury, the mean (SD) EQ-5D utility scores at 3 months after the injury decreased from 0.6 (0.2) to 0.35 (0.24) in a Canadian study and 0.43 (0.34) to 0.39 (0.35) in a German study . The EQ-5D utility scores in the current study were even lower, most likely because of the added criteria of frailty.…”
Section: Discussionmentioning
confidence: 58%
“…With the abundant resource of femoral fracture patients undergoing internal fixation, our hospital had rich experience in operating room nursing and found that routine operating room nursing placed emphasis on the doctor's procedure with the main purpose of assisting the doctor to finish the procedure, and so did the clinical practice, so routine operating room nursing was passive and limited to some extent and could not meet the gradually increasing nursing needs from current social and medical development. The clinical quantitative assessment strategy is the condition quantitative assessment scale generated on the basis of the evidence-based medicine and evidence level, which can fully consider the individual situation of patients and carry out multidimensional evaluation to perform systematic nursing intervention according to the physiological and psychological status of patients, making clinical nursing more scientific, comprehensive, and efficient [ 21 – 24 ]. To further improve the clinical nursing level of our hospital, WeChat health education was implemented for femoral fracture patients during the perioperative period, which promoted the intensity of nursing intervention and obviously improved patients' psychological state, self-care ability, etc.…”
Section: Discussionmentioning
confidence: 99%